ECONOMIC METHODS OF THE ENVIRONMENT QUALITY REGULATION IN RUSSIA - TATIANA OLEGOVNA Tagaeva; VADIM MANAVIROVICH Gilmundinov; LYDIA KUZ’MINICHNA Kazantseva (Мир новой экономики)
The article analyzes the modern ecological situation in the Russian Federation and its negative impact on the health of Russian citizens. Results of the forecast emissions, depending on the different scenarios of economic development of the Russian Federation are given - pessimistic and optimistic. In implementing the latter one is to wait a further increase in the load on the environment. To prevent it, it is necessary to improve of state of environmental policy. The article discusses the need for the following areas of development: improving environmental institutional structures and introducing a series of organizational measures, raising the efficiency of the mechanism of payments for negative impact on the environment, the introduction of economic instruments stimulating environmental mechanism, and others.